Analysing the Speed-flow Relationship in Urban Road Traffic - Juhász, M.; Koren, Cs; Mátrai, T (Acta Technica Jaurinensis, 2016)
In road traffic, speed-flow curves describe the relationship between vehicle flow rates and average vehicle speeds. These functions are one of the basic elements of transport modelling and they are widely used in project appraisal. Review and re-validation of speed-flow relationship has become timely in recent years as vehicle fleet changed, average traffic volumes increased and more comprehensive, automatic data collection became available. This study used the database of the road operator in Budapest to simultaneously analyse travel times and traffic volumes. The paper aims to examine the validity of the well-known fundamental diagram for urban roads, to provide an estimation for the speed-flow curve based on the Budapest case and to assess the on-set process of congestion.